MGMT promoter methylation analysis for allocating combined CCNU/TMZ chemotherapy: Lessons learned from the CeTeG/NOA‐09 trial. Issue 7 (10th November 2020) - Tzaridis, Theophilos; Schäfer, Niklas; Weller, Johannes; Steinbach, Joachim‐Peter; Schlegel, Uwe; Seidel, Sabine; Sabel, Michael; Hau, Peter; Seidel, Clemens; Krex, Dietmar; Goldbrunner, Roland; Tonn, Jörg‐Christian; et al.
Abstract: The CeTeG/NOA‐09 trial showed a survival benefit for combined CCNU/TMZ therapy in MGMT‐promoter‐methylated glioblastoma patients (quantitative methylation‐specific PCR [qMSP] ratio > 2). Here, we report on the prognostic value of the MGMT promoter methylation ratio determined by qMSP and evaluate the concordance of MGMT methylation results obtained by qMSP, pyrosequencing (PSQ) or DNA methylation arrays (MGMT‐STP27). A potential association of qMSP ratio with survival was analyzed in the CeTeG/NOA‐09 trial population (n = 129; log‐rank tests, Cox regression analyses). The concordance of MGMT methylation assays (qMSP, PSQ and MGMT‐STP27) was evaluated in 76 screened patients. Patients with tumors of qMSP ratio > 4 showed superior survival compared to those with ratios 2‐4 ( P = .0251, log‐rank test). In multivariate analysis, the qMSP ratio was not prognostic across the study cohort (hazard ratio [HR] = 0.88; 95% CI: 0.72‐1.08). With different cutoffs for qMSP ratio (4, 9, 12 or 25), the CCNU/TMZ benefit tended to be larger in subgroups with lower ratios (eg, for cutoff 9: HR 0.32 for lower subgroup, 0.73 for higher subgroup). The concordance rates with qMSP were 94.4% (PSQ) and 90.2% (MGMT‐STP27). Discordant results were restricted to tumors with qMSP ratios ≤4 and PSQ mean methylation rate ≤25%. Despite a shorter survival in MGMT‐promoter‐methylated patients with lower methylation according to qMSP, these patients had a benefit from combined CCNU/TMZ therapy, which even tended to be stronger than in patients with higher methylation rates. With acceptable concordance rates, decisions on CCNU/TMZ therapy may also be based on PSQ or MGMT‐STP27. Abstract : What's new? In patients with IDH‐wildtype glioblastoma, methylation of the MGMT promoter allows for improved survival after chemotherapy, due to reduced ability to repair DNA damage. Here, the authors set out to evaluate the use of different tests for promoter methylation, with an eye toward their usefulness at allocation of chemotherapy, and on their prognostic applicability. They show that three different methods of testing methylation—quantitative methylation‐specific PCR, pyrosequencing, and DNA methylation arrays—agree more than 90% of the time. Patients with lower MGMT promoter methylation had shorter survival times, but still benefited from CCNU/TMZ therapy.